2019
DOI: 10.1007/s00277-019-03830-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-agent ibrutinib in RESONATE-2™ and RESONATE™ versus treatments in the real-world PHEDRA databases for patients with chronic lymphocytic leukemia

Abstract: After analyzing treatment patterns in chronic lymphocytic leukemia (CLL) (objective 1), we investigated the relative effectiveness of ibrutinib versus other commonly used treatments (objective 2) in patients with treatment-naïve and relapsed/refractory CLL, comparing patient-level data from two randomized registration trials with two real-world databases. Hazard ratios (HR) and 95% confidence intervals (CIs) were estimated using a multivariate Cox proportional hazards model, adjusted for differences in baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The benefit demonstrated with ibrutinib in clinical trials has also been observed in the real-world setting [20][21][22][23][24][25][26][27][28][29][30][31] . However, most real-world evidence came from studies in R/R CLL 20, 25-27, 30, 31 , including reports where ibrutinib was used in compassionate use programs 24,27,30,31 and from single-site experience 22,26 .…”
Section: Introductionmentioning
confidence: 92%
“…The benefit demonstrated with ibrutinib in clinical trials has also been observed in the real-world setting [20][21][22][23][24][25][26][27][28][29][30][31] . However, most real-world evidence came from studies in R/R CLL 20, 25-27, 30, 31 , including reports where ibrutinib was used in compassionate use programs 24,27,30,31 and from single-site experience 22,26 .…”
Section: Introductionmentioning
confidence: 92%
“…[2][3][4] Clinical management of patients with R/R CLL or with treatment-naive CLL harbouring high-risk genetic features has been revolutionized by the irreversible Bruton's tyrosine kinase (BTK) inhibitor ibrutinib which confers remarkable response rates both in first-line and in previously treated patient cohorts. [5][6][7][8][9] Although clinical trials and the analyses of real-world patient cohorts have shown a survival advantage with ibrutinib over standard therapies, 6,7,[10][11][12][13] durable remission is eventually followed by either Richter's transformation or progressive CLL in a subset of the patients. While Richter's transformation tends to occur during the first or second year of ibrutinib treatment and its cumulative incidence shows a plateau after the third year, CLL progression emerges later, typically after a 12-15-month period of BTK inhibition with events regularly occurring during the third, fourth and fifth years after therapy initiation.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was discussed at length by Backenroth 22 with published examples also available. 23,24 Rebalancing the external control arm to minimize the mean absolute error in the number of prior lines of therapy between data sets. This is a modification of the random line approach, whereby 1 line is selected per patient but with the objective of minimizing the difference in the number of prior lines between the external control and intervention data sets.…”
Section: Methods For Comparisonmentioning
confidence: 99%
“…This approach was discussed at length by Backenroth 22 with published examples also available. 23,24…”
Section: Methodsmentioning
confidence: 99%